2011
DOI: 10.1038/aps.2011.105
|View full text |Cite
|
Sign up to set email alerts
|

Platonin inhibited PDGF-BB-induced proliferation of rat vascular smooth muscle cells via JNK1/2-dependent signaling

Abstract: Aim: To examine the inhibitory actions of the immunoregulator platonin against proliferation of rat vascular smooth muscle cells (VSMCs). Methods: VSMCs were prepared from the thoracic aortas of male Wistar rats. Cell proliferation was examined using MTT assays. Cell cycles were analyzed using flow cytometry. c-Jun N-terminal kinase (JNK)1/2, extracellular signal-regulated kinase (ERK)1/2, AKT, and c-Jun phosphorylation or p27 expression were detected using immunoblotting. Results: Pretreatment with platonin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…8,27 In VSMCs, these responses are initiated when PDGF-BB induces the activation of downstream signaling molecules, such as by phosphorylation of ERK1/2 and p38. 7 Our data show that piperine reduces the phosphorylation of ERK1/2 in PDGF-BB-stimulated VSMCs in a dose-dependent manner and upregulates p27 kip1 expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,27 In VSMCs, these responses are initiated when PDGF-BB induces the activation of downstream signaling molecules, such as by phosphorylation of ERK1/2 and p38. 7 Our data show that piperine reduces the phosphorylation of ERK1/2 in PDGF-BB-stimulated VSMCs in a dose-dependent manner and upregulates p27 kip1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Recently, studies have reported that PDGF-BB contributes to intracellular signaling through mitogen-activated protein kinases (MAPKs) in various cells. 8,9 VSMC migration and proliferation are also influenced by activated MAPKs, such as extracellular signalregulated kinase (ERK)1/2 and p38 MAPK. 10,11 Moreover, ROS are involved in the proliferation and migration of PDGF-BB-stimulated VSMCs.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, tyrosine-phosphorylated PDGF receptors interact with several other cytoplasmic proteins that constitute Src homology 2 domains, including phospholipase C␥, ras guanine 5=-triphosphatase-activating protein, phosphatidyl-inositol 3-kinase, and tyrosine phosphatase SHP-2 (5). These signaling molecules mediate cellular activities, including proliferation, migration, and differentiation in response to PDGF (5). Furthermore, PDGF transmits its signals to the intracellular space through activation of AKT and MAPKs (5).…”
mentioning
confidence: 99%
“…These signaling molecules mediate cellular activities, including proliferation, migration, and differentiation in response to PDGF (5). Furthermore, PDGF transmits its signals to the intracellular space through activation of AKT and MAPKs (5). MAPKs phosphorylate JNKs, which in turn results in the phosphorylation of many transcription factors, including the c-Jun component of the activator protein-1 transcription family (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation